Pengembangan Media Pembelajaran Berbasis Aplikasi Program Autocad Dalam Kompetensi Dasar Jenis-Jenis Gambar Potongan Pada Mata Pelajaran Gambar Teknik di SMK Negeri 1 Sitolu Ori - Osama Fakta Finish Ndruru; Yelisman Zebua; Arisman Telaumbanua; Adrianus Zega (Journal on Education, 2023)
Technical drawing subject is one of the subjects at SMK Negeri 1 Sitolu Ori expertise competency in Modeling Design and Building Information that encourages students to have good and precise drawing skills. Students are confused in drawing a part of the building, and students have difficulty understanding the details of drawing parts. The purpose of this research is to improve the use of learning media in form of video tutorials based on AutoCAD applications on the material of the types of drawing parts. The model used in this research is Sugiyono's development model, the first step of potential and problems obtained through observation, the second step of collecting information to obtain various information of data, the third step of product design which it is method of making / designing products, the fourth step of design validation is carried out by validators, the fifth step of design revision is carried out from assessment results from the validators, the sixth step of product trials involving students and teachers to assess the products developed and the seventh step of revision of product trial results is carried out by finishing the product. Based on results of research, the learning media developed has been tested and assessed by validators with the acquisition of scores from media experts 92.94%, material experts 95.29%, and linguists 100% with very feasible to use, then the media is very practical to use by students with a percentage of 83.3% and a percentage of the involved teacher of 89.23%. The media is also effective to use with a percentage of completeness of 81.82%. As the results of this research, the learning media developed based on the AutoCAD program application has met the research objectives